Corneal ulcer caused by Pseudomonas pseudomallei: report of three cases. - Siripanthong, S; Teerapantuwat, S; Prugsanusak, W; Suputtamongkol, Y; Viriyasithavat, P; Chaowagul, W; Dance, D; White, N (1991)
We report three cases of corneal ulcer caused by Pseudomonas pseudomallei. In all cases corneal trauma preceded the development of extensive ulcers, subconjunctival abscesses, and hypopyon. Treatment for a total of 8 weeks with topical and/or parenteral ceftazidime followed by amoxicillin-clavulanic acid produced resolution of infection in each case.